Swimming speed distributions of bull spermatozoa as determined by quasi-elastic light scattering. - Hallett, F R (1978)
88 semen samples from 39 bulls have been investigated by the quasi-elastic light scattering technique. Normal, defective, and dead cells each yielded characteristic autocorrelation functions. The form of these functions indicates that the swimming speed distribution of normal cells is a gamma distribution with two degrees of freedom while that for defective or circular swimmers is a gamma distribution with one degree of freedom. The resulting analysis of the experimental autocorrelation functions yields the fraction of the sample that is normal, the fraction that is defective, and the average speed of each group. The average helical swimming speed of normal cells was found to be 384 micron/s, while the average trajectory speed of the circular swimmers was found to be 103 micron/s. The overall quality of the semen samples as determined by light scattering is compared to quality determination on the same samples by technicians from the artificial insemination industry.